Pandawan Website Design Based Content Management System As Media E-commerce Transaction - Bein, Adrian Sean; Graha, Yuliana Isma; Pangestu, Anggit Panji (Pandawan, 2020)
As the Regulation of the Minister of Research, Technology and Higher Education of the Republic of Indonesia No. 9 of 2018 concerning the accreditation of scientific journals article 4 which mentions the requirements of scientific journals, it has been announced on the official website page of ARJUNA (National Journal Accreditation), that regarding the Circular of the Director of Intellectual Property Management Number 101 / E5.2 / SE / 2018 dated 18 January 2018 regarding Accreditation of Scientific Periodicals only accepts and processes the proposed national scientific (periodical) journal accreditation that has been managed electronically, so that the assessment process will be easier, faster, accurate and transparent (ARJUNA, 2018). But in reality in the era of the industrial revolution 4.0, the Government was not well organized. There are a total of 3 (three) problems from 2 (two) sides of website users, namely there are still many institutions or agencies that in the management use conventional processes so that people who want to publish their articles digitally are constrained with limited access, there are still minimal agencies that have not been able to provide a forum to provide educational support facilities and Open Journal System (OJS) in the form of attractive website-based e-commerce. In this study there are 2 (two) data collection methods, namely observation and literature study methods. The results of this study are Pandawan e-commerce based websites that provide journal publisher services that can be managed online, as well as solving publisher problems in managing journals online.